On Henrikas Nagys’ Niveau - Bernotienė, Gintarė (Colloquia, 2020)
The author of the article examines the trajectories of the Lithuanian diaspora poet, Henrikas Nagys’ (1920–1996), works, their recognition and his ability to remain an influential figure in the field of literature. The assessment of poet’s works and his personality are highlighted by introducing behindthe-scenes actions and circumstances, which did not resonate in the literary criticism of the time, but were captured in the diaspora cultural press and in the private egodocuments that became available later, such as memoirs, diaries, and vast correspondence. These egodocuments constitute the basis of this research. The author of the article has chosen the historical empirical method, which suits the most to observe the dynamics of Nagys’ aesthetic and moral choices and evaluations in the context of Lithuanian diaspora—the early recognition of Nagys’ poetry; the strengthening of his generation’s literary position, actively pursued by the poet himself; promoting the authors of similar poetic aesthetics to the ranks of the leading writers (i.e. hierarchical actions); and later, poet’s sore reaction to his exclusion from the top of hierarchy. Nagys, an ardent patriot of Lithuania, who firmly defended his position in the disputes, was uncompromising towards the Soviet regime. Ideological and worldview differences were one of the reasons why Nagys broke ties with the associates of the monthly Akiračiai and the literary journal Metmenys and the Santara Federation. Nagys felt unappreciated when the literary criticism professing the new literary research methods put forward the authors of the renewed canon of Lithuanian diaspora poetry (Alfonsas Nyka-Niliūnas, Tomas Venclova, Henrikas Radauskas). Nagys learned of the value of his works and of his influence on poets living in Lithuania only after 1990s, relying on the reactions to his poetry (political context was also important for understanding its value orientation) revealed in private correspondence with Lithuania’s writers.